(untitled) (Vietnam Journal of Community Medicine, 2022)
A descriptive study with 2 cross-sectional descriptions 3 months duration at Chau Thanh Medical Center, Hau Giang province. A group of 300 outpatients are selected. Research method: using direct interview questionnaire and retrospective clinical records. The results show that: Compliance rate is quite low: 30%. A number of factors clearly reduce the patient’s adherence to treatment, such as: low education level, old age, poor family economic situation. Adherence counseling activities are still limited, the proportion of patients being consulted and being able to follow is only 54%. This can be a elementary contribute to lower compliance rates. Due to low compliance with value adjustment, the percentage of people who met the treatment target for blood sugar testing was very low at only 15.2% even after counseling and 5.1% amongst the once without counseling. Allows users who follow the consult of nurces lead to increase the percentage of patients achieved target of blood sugar by 3 times. Conclusion: The low compliance rate is caused by advanced age, low education and completion. poor family economic situation. Thanks to increased counseling and increased compliance rates and improved blood sugar index.